Managing Student Diversity in Business Education: Incorporating Campus Diversity into the Curriculum to Foster Inclusion and Academic Success of International Students - Zhang, M.; Xia, J.; Fan, David; Zhu, J. (-, 2015)
The past three decades have witnessed significant growth of culturally and linguistically diverse international students in Organization for Economic Co-operation and Development countries. International students now constitute an important component of the student body at many universities, especially in their business schools. The increased presence of international students has generated new demands and challenges for these business schools, and a number of issues related to international students have been identified in the literature. However, the increased presence of international students has not led universities and business schools to develop adequate responses to the issues and make subsequent changes in the curriculum. Diversity on campus continues to be managed in roughly the same way as in business organizations. Drawing on the notion that diversity should be defined and understood in terms of context, this conceptual paper redefines diversity on campus, identifies limitations of current diversity education in the higher education context, and develops a competency-oriented approach to improve inclusion and academic performance of international students.